Infrastructure, mobility and safety 4.0: Modernization in road transportation. (November 2021) - Duggal, Angel Swastik; Singh, Rajesh; Gehlot, Anita; Gupta, Lovi Raj; Akram, Sheik Vaseem; Prakash, Chander; Singh, Sunpreet; Kumar, Raman
Abstract: This study explores the modernization of road-based technologies for the enhancement of mobility while also implementing safer transportation. Mobility plays a critical role in everyday life on a micro and a macro scale combined. Modernization in mobility would enable establishment of a sustainable, digitalized and informed society. The inclusion of AI/ML to enhance road environment, curbing driver distraction, adopting electric vehicles, and integrating low power computing units in vehicular networks are among the potential recommendations for strengthening the evolving digital road architecture. The current ecosystem surrounding road safety and mobility can be boosted even further upon integrating products of modern technology into the classical elements of transportation. Modern technologies are classified and perceptually investigated by realizing the current challenges and proposing seamless potential extensions to the existing infrastructure from each domain. Techno-administrative concepts like the regulation of individual risk profiles for achieving a safer road environment are addressed. Highlights: To explore the digitalization of road-based technologies for the enhancement of mobility and safer environment. Technologies classification for achieving the target of digitalization and possible solution with the specific technology. Regulation of risk profile for achieving the safer road environment and inclusion of AI/ML. Recommendations for integrating low power computing units in vehicular networks to digitalizing road.